Subacute spongiform encephalopathy: Electron microscopic studies - Bubis, J. J. (1972)
Electron microscopic changes in brain biopsies from two cases of subacute spongiform encephalopathy are described. Large vacuoles seen in astrocytic and neuronal processes were surrounded by one or more concentric membranes. Dense-core vesicles were found in axonal endings and in nerve cell perikarya; these particles could represent catecholamine-containing vesicles.